Formulasi Buah Tampoi (Baccaurea macrocarpa) dalam Sediaan Masker Gel sebagai Antiaging - Ika Avrilina Haryono; Noval Noval; Bayu Nugraha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Antioxidants are able to suppress free radicals, reducing the occurrence of oxidation reactions, and are also effective in preventing skin damage due to the aging process. The use of tampoi fruit extract as a gel mask preparation could have a purpose as an antioxidant to treat skin problems. The method is an experimental laboratory by making a gel mask preparation from tampoi fruit. The making of a gel mask begins with mixing the base mask consisting of PVA (Polyvinyl Alcohol), Propylene Glycol, Carbomer 940 then added with tampoi fruit extract. The tampoi fruit gel mask formulation in this study was made based on variations in PVA of FI (3%), FII (6%), FIII (12%), and FIV (18%) which aims to determine its effect and the most optimal formula. The steps taken include the extraction of tampoi fruit, making gel masks with 4 formulas F1 (3%), F2 (6%), F3 (12%), and F4 (18%) followed by evaluation of formulas which include organoleptic tests, pH test, viscosity test, spreadability test, and adhesion test. Physical stability testing was carried out for 4 weeks. Furthermore, the data were analyzed by using the ANOVA statistical test. The results showed that there was a significant effect on the evaluation of the viscosity test and the adhesion test for each formula. Meanwhile, the pH test and spreadability test did not have a significant effect on each formula. The optimal formula is in F1 with a PVA concentration of 3%.